Repas of rip-off? : an initial advocacy position... on the EPA negotiations (Caribbean Policy Development Centre St. MichaelBB, 2004)
Looks at the major challenges facing the Caribbean as it proceeds into the Phase 11 negotiations and at what should be a Caribbean initial response to the positions being enunciated by the EU. Seeks to clearly outline the Caribbean NGOs' philosophical position on the objectives and goals of any economic partnership agreement with Europe. Suggests specific sectoral recommendations.
Keywords: FOREIGN TRADE